Full runner electrolyzer stack for industrial-current-density NOx −-mediated ammonia synthesis from air and water - Wei Liu; Yang Lv; Honghui Ou; Jiqiu Zhang; Yuxi Ren; Mengyang Xia; Yang Li; He Li; Xiaoling Ren; Huagui Hu; Guidong Yang (Nature Communications)
Abstract Plasma-electrochemical tandem conversion with NOx − as intermediates promises a route for renewable ammonia (NH3) synthesis from air and water. However, a critical challenge lies in developing electrolyzers capable of operating efficiently at large current densities. Here, we present a scalable membrane electrode assembly electrolyzer with a full runner design (MEA-FR) that achieves efficient NH3 production at industrial current densities. Compared to conventional serpentine runner configuration, MEA-FR leveraging forced convection within porous electrodes achieves three-order-of-magnitude enhancement in NOx − mass transfer flux. This design, meanwhile, generates strong shear forces across the porous electrode, promoting rapid detachment of O2 bubbles at the anode and reducing overpotential losses. Notably, MEA-FR exhibits a high Faradaic efficiency of 91.8 ± 1.4% for NH3 synthesis at 500 mA cm−2, significantly outperforming the serpentine runner counterparts (64.9 ± 1.1%). Furthermore, a scaled-up 4 × 25 cm2 MEA-FR stack with four modular cells is assembled with rotationally symmetric bipolar plates, delivering high NOx − conversion efficiency (>95%), high Faradaic efficiency (>91%), and long-term stability (>200 h) under industrial-relevant current densities.